1997
DOI: 10.2135/cropsci1997.0011183x003700060036x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Gibberellins Retard Growth of Cool‐Season Turfgrasses†

Abstract: Several modified gibberellins which inhibit shoot elongation have been assessed as turfgrass growth retardants. Dichloro‐methano 16,17‐dihydro GA5 (DMDGA5) effectively inhibited growth of the cool season grasses, Festuca arundinacea Schreb., Poa pratensis L., and Lolium perenne L. Turf growth (weekly cutting dry weight) was reduced by up to 70% in three separate field trials over three seasons. This inhibition lasted up to 5 wk before recovery to control growth rates and, often, there was then a transient enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Foreman and Marshall (1990) showed N‐t‐butylcarbonyl‐N‐(4′‐chlorophenyl methyl) aminopyrazine, another GA inhibitor, reduced leaf length of perennial ryegrass ( Lolium perenne L.) without altering mesophyll cell number. Since there is no suggested or reported evidence that TE reduces cell wall deposition, suppression of cell enlargement by TE (King et al, 1997) may have increased the relative total cell wall content. This phenomenon could enhance wear tolerance and account for the increased rigidity of TE‐treated turf compared with untreated turf (unpublished data, 1993–1996).…”
Section: Resultsmentioning
confidence: 99%
“…Foreman and Marshall (1990) showed N‐t‐butylcarbonyl‐N‐(4′‐chlorophenyl methyl) aminopyrazine, another GA inhibitor, reduced leaf length of perennial ryegrass ( Lolium perenne L.) without altering mesophyll cell number. Since there is no suggested or reported evidence that TE reduces cell wall deposition, suppression of cell enlargement by TE (King et al, 1997) may have increased the relative total cell wall content. This phenomenon could enhance wear tolerance and account for the increased rigidity of TE‐treated turf compared with untreated turf (unpublished data, 1993–1996).…”
Section: Resultsmentioning
confidence: 99%
“…showed that these compounds are as effective as trinexapac-ethyl in reducing growth in cooLseason turfgrasses (King et al, 1997).…”
Section: Chemicalsmentioning
confidence: 97%
“…16, (Fig. 1) and other ring D-modified GA 5 derivatives (Mander et al, 1995(Mander et al, , 1998a(Mander et al, , 1998b are structurally very similar to GA 20 .When these ring D-modified GAs are applied to many higher plant species, and especially to grasses, they can effectively inhibit shoot growth (Evans et al, 1994a(Evans et al, , 1994bTakagi et al, 1994;Foster et al, 1997;King et al, 1997King et al, , 2004. Associated with the reduction in shoot elongation is a concomitant reduction in levels of endogenous 3b-hydroxylated GAs and an increase in one or more of the 3-deoxy precursors (Foster et al, 1997;Junttila et al, 1997;Zhou, 2000).…”
mentioning
confidence: 95%